Hubungan Komitmen Beragama Dengan Kesejahteraan Psikologis Pada Masyarakat Jakarta Usia Dewasa - Hapsarini Nelma; Dini Rahma Bintari; Fivi Nurwiyanti (Universitas Muria Kudus, 2012)
This study focuses on the relationship between religious commitmentto the psychological well-being. The research was done because of the increasing phenomenon of religious activity in the city as a result of the psychological burden caused by the problems in the city. This study used 124 subjects with a characteristic residence in Jakarta, the minimum high school education, aged 24-65 years. This study is a quantitative study using a correlation calculation to determine the relationship between two variables. The results of this study showed a significant relationship between religious commitment to the psychological well-being